The Politics of Memory: Perception and Imageability of Cano City - Shema, Abdulsalam I.; Balarabe, Muhammad K.; Atanda, Jubril O. (ICONARCH International Congress of Architecture and Planning, 2017)
This paper approaches the question of understanding the memory of politics in Kano city with its architectural and natural surroundings in reference to, politics, memory, imageability, environment, perception and subjective experience (radical observation) based on phenomenological inquiry. Kano is a city in the northern part of Africa most populous country, Nigeria. The memory shaping in community community here deals with, how people identify and form a common bond, narrative and heritage. This paper tends to analyse the memory of politics in an enmeshed experience of Kano city, explaining Kano in precolonial times, colonial and post-colonial era (African, Islamic and western heritage). Enmeshed experience can be defined as the understanding of paradoxes of the notion of identity through which phenomenology points out in relation to the interwoven network of events related to the city. Also, it would examine the city, as a historical environment, stating its importance, time, space, culture and physical attributes and its city image been represented and promoted in a global world. To observe Kano, the place-memory seeing it through political influence, its urban transformation, cultural and economic settings, time and space as a political factor will be analysed through perspective experience, imageability, phenomenological inquiry and radical observation. However, a continuous unfolding overlapping of spaces with material and technology and detail (city narration, photographic images) will be used to interpret the environmental potential and radical observation. Kano is a historical city rich in cultural codes with difference ethnic and religious background, this would, therefore, enhance in experiencing of the city through bodily experiences motives, in order to discover the political flow of memory with the cityscape.